A proclamation : Information having reached the office of the Executive of said Territory, through various sources, to the effect that combinations of men have been and are now being made with a view to entering and occupying the region of country ... I, Edwin S. McCook, Secretary and Acting Governor of the United States ... warn all such unlawful combinations of men, of whatever loyality, or under whatever plea or excuse operating ... violate our Treaty stipulations with these Indians ... Given at my office in the city of Yankton, this 6th day of April A.D. 1872 . ([Publisher not identified], 1872)
Warning from Acting Governor Edwin S. McCook to persons who oppose the Indian reservations in the Black Hills of Dakota.